PENGARUH PERBEDAAN PADAT TEBAR TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN NILA (Oreochromis niloticus) - Maulida Riana (Fakultas Pertanian Universitas Samudra, 2021)
Tilapia (Oreochromis niloticus) is one of the freshwater aquaculture commodities that has promising business prospects. Currently, tilapia has spread to tropical and subtropical countries, while in cold climates tilapia cannot live well. Tilapia cultivation is relatively easy and has several advantages in cultivation such as relatively fast growth, easy to develop and easy to adapt. This study aims to determine differences in stocking density on the growth and survival of tilapia (Oreochromis niloticus) fry. The method used was Completely Randomized Design (CRD) with 4 treatments and 3 replicates P1 (5 fish/container), P2 (15 fish/container). container) , P3 (25 fish/container) and P4 (35 fish/container). The parameters observed during the study were survival, and growth. The results of the treatment significantly affected survival, absolute weight growth, absolute length growth and daily growth rate. The best survival rate is shown in P1 which is 66.67% and the lowest percentage is in P4 treatment, which is 47.62%. The best absolute weight growth was found in P1 which was 5.04 g and the lowest absolute weight growth was in P4 treatment, which was 2.24 g. The absolute length growth showed the best results obtained at P1 which was 1.06 cm, while the lowest absolute length growth was found at P4 which was 0.71 cm. The best daily growth rate was found in P1 which was 16.81 gr and the lowest daily growth rate was found in P4 treatment, which was 7.48 gr